Comparative Study on the Thermal Performance of Three Aedes aegypti (Diptera: Culicidae) Populations From Argentina. Issue 4 (2nd March 2021) - De Majo, María Sol; Zanotti, Gabriela; Gimenez, Javier O; Campos, Raúl E; Fischer, Sylvia
Abstract: The distribution of Aedes aegypti (L.) (Diptera: Culicidae) is expanding towards colder regions, which could be aided by an adaptation of the immature stages to the local thermal conditions. This study aimed to assess the developmental success at different temperatures in three populations of Ae. aegypti located across a climate gradient in Argentina. Survival to the adult stage, development time, and wing length at 14, 18.5 and 24°C were compared among three populations of Argentina: Resistencia in the subtropical region, and Buenos Aires and San Bernardo in the temperate region. Survival was similar between populations and equal to or higher than 69%, and increased at higher temperatures within the studied range. Development times were similar between populations. A negative effect of temperature was observed and the reduction of development time at increasing temperatures was stronger for males than for females. Wing lengths were negatively affected by increasing temperatures, and the reduction of wing length was stronger for females than for males. Also, the reduction of wing lengths with temperature was stronger for San Bernardo and Resistencia than for Buenos Aires, and differences between sexes were larger for Resistencia than for Buenos Aires or San Bernardo. Although the results do not evidence differences in survival and development time between temperate and tropical populations, the three populations have a higher tolerance to low temperatures than the populations from other regions.